Characteristics and risk markers of specific learning disorders in Finnish specialised health care: A national register-based study - Arrhenius, Bianca (fi=Turun yliopisto|en=University of Turku|, 2022)
Background: Specific learning disorders are common, with prevalence estimates of 3–15% among school children. Despite this, national population-based studies on the risk factors for specific learning disorders are scarce. Aims: This thesis examined the cumulative incidence and gender distribution of specific learning disorders as well as their associations with maternal social risk markers, prenatal smoking, maternal vitamin D levels during pregnancy, and the child’s relative age. Methods: The sample comprised a source cohort of all children born in Finland 1996–2007 (N = 690,654) and among them, those who were diagnosed with specific learning disorders in specialised services, i.e., reading, arithmetic, or spelling disorder, or a mixture of these (ICD-10 codes F81.x) by the end of 2012 (n = 6,490). The data was retrieved from national registers. Results: The cumulative incidence was 1.55% for specific learning disorders diagnosed in specialised services by age 15, and the disorders were twice as common among boys. Common comorbidities were developmental disorders of speech, language and coordination (40.4%), and psychiatric disorders (38.4%). Decemberborn children, the youngest in class, were diagnosed 1.77-fold compared to Januaryborn children. Significant associations were found for specific learning disorders and low maternal socioeconomic status, educational level, and single motherhood. Smoking during pregnancy was associated with specific learning disorders when comparing cases to population controls, but the association did not persist when comparing differentially exposed siblings. No association was found between prenatal vitamin D deficiency and specific learning disorders. Conclusions: The clustering of social risk factors and specific learning disorders needs to be acknowledged in health care and educational service planning. The relative age effect on specific learning disorder diagnoses implies a need to standardise diagnostic procedures, and further research on the benefits of flexible school start timing. Maternal smoking and vitamin D deficiency during pregnancy might not be causal aetiological risk factors for specific learning disorders.

Erikoissairaanhoidossa todettujen oppimishäiriöiden yleisyys ja riskitekijät: kansallinen rekisteripohjainen tutkimus Tausta: Oppimishäiriöitä esiintyy arviolta 3–15% kouluikäisistä lapsista. Yleisyydestään huolimatta kirjallisuudesta puuttuu väestön kattavia tutkimuksia vallitsevuudesta sekä oppimishäiriöiden varhaisista riskitekijöistä. Tavoitteet: Tämä väitöskirja tutki erikoissairaanhoidossa diagnosoitujen oppimishäiriöiden kumulatiivista ilmaantuvuutta, sukupuolijakaumaa sekä yhteyksiä sosiaalisten riskitekijöiden, raskaudenaikaisen tupakoinnin, äidin D-vitamiinitasojen sekä lapsen nuoren suhteellisen iän välillä. Menetelmät: Tutkimusdata koottiin kansallisista rekistereistä. Otos sisälsi kaikki Suomessa vuosina 1996–2007 syntyneet lapset (N = 690,654). Heidän joukostaan poimittiin ne, joilla todettiin oppimishäiriö, eli lukemisen, kirjoittamisen tai matematiikan oppimisvaikeus tai näiden yhdistelmiä (ICD-koodit F81.x) erikoissairaanhoidossa vuoteen 2012 loppuun mennessä (n = 6,490). Tulokset: Oppimishäiriöiden kumulatiivinen esiintyvyys oli 1.55% 15 ikävuoteen mennessä, ja ne olivat tuplasti yleisempiä pojilla. Päällekkäisyys kielellisten ja motoriikan häiriöiden (40.4%) sekä psykiatristen häiriöiden (38.4%) kanssa oli yleistä. Luokan nuorimmilla eli joulukuussa syntyneillä lapsilla todettiin oppimishäiriöitä 1.77-kertaisesti tammikuussa syntyneisiin verrattuna. Merkitseviä yhteyksiä löytyi oppimishäiriöiden ja äidin matalan koulutustason, sosioekonomisen aseman sekä yksinhuoltajuuden välillä. Yhteys raskaudenaikaisen tupakoinnin ja oppimishäiriöiden välillä havaittiin tapaus-verrokki asetelmassa, mutta yhteys hävisi kun verrattiin eri lailla tupakoinnille altistuneita sisaruksia. Äidin raskaudenaikaisen d-vitamiinitason ja lapsen oppimishäiriön välillä ei löytynyt yhteyttä. Päätelmät: Oppimishäiriöiden ja sosiaalisten riskitekijöiden kasaantuminen on tärkeä huomioida terveys- ja koulutuspalveluiden suunnittelussa. Nuoren suhteellisen iän vaikutusta diagnostiikkaan voisi mahdollisesti vähentää kehittämällä kansallisia hoitosuosituksia sekä lisäämällä koulunaloituksen ajankohdan joustavuutta. Raskaudenaikainen tupakointi ja d-vitamiinitasot eivät tämän tutkimuksen perusteella näytä olevan syy-yhteydessä oppimishäiriöihin.